Improvement of bit error rate performance of MC-CDMA system by using adaptive digital modulation schemes - T, Jaya; Monisha, M; Meena, M; Sharanya, C (International Journal of Engineering and Technology, 2018)
In Wireless Communication, the transmission channel suffers due to multipath propagation and channel dispersion due to Inter Symbol Interference (ISI), thereby degrades the system performance greatly. Future communication requires high data rate and effective utilization of bandwidth. Hence, there is a need to improve the Bit Error Rate (BER). The proposed work is Adaptive Modulation (AM), combined with Multi Carrier Code Division Multiple Access (MC-CDMA) based transmission system. It is a promising way to increase the data rate and it uses bandwidth in a efficient manner. The Adaptive Modulation based MC-CDMA systems applied to a wide-area environment, can achieve high data rate up to 100Mbps. In this paper M-ary PSK, M-ary QAM and M-ary CPM modulation techniques are used. The Adap-tive modulation based MC-CDMA systems perform well for around 10 number of users. As a whole, the adaptive MC-CDMA system is found to give the optimum BER performance of given digital modulation schemes for fourth generation environment.Â Â